Silane-modified surfaces in specific antibody-mediated cell recognition - Sterzynska, Karolina; Budna, Joanna; Frydrych-Tomczak, Emilia; Hreczycho, Grzegorz; Malinska, Agnieszka; Maciejewski, Hieronim; Zabel, Maciej (Folia histochemica et cytobiologica, 2014)
The immobilization of antibodies on various surfaces has been the subject of advanced research in various immunoassay-based diagnostic devices. The physical and chemical stabilities of the immobilized antibodies on a solid surface still cause many problems because upon immobilizing antibody molecules, the antigen-binding ability usually decreases. The silanization of surfaces with organosilanes carrying chemically active groups such as (3-aminopropyl) triethoxysilane (APTES) can accommodate these antigen-binding molecules in an appropriate orientation so that their functionality and binding activity are essentially retained. In this study, n-butyltrimethoxysilane (BMS) and 3-(octafluoropentyloxy)-propyltriethoxysilane (OFPOS) were used as "blocking silanes". The aims of this study were to compare the effectiveness of specific antibody binding of APTES, APTES + BMS and APTES + OFPOS and to characterize the modified surfaces by contact angle measurements and immunofluorescence measurements prior to and after immobilizing proteins. Additionally, we have evaluated the functionality of the immobilized antibodies by their abilities to bind EpCAM-positive human colon adenocarcinoma cell line (LoVo) and EpCAM-negative mouse embryonic fibroblast cell line (3T3). Cell enumeration was conducted on the basis of DAPI-positive signals and recorded using a confocal laser scanning biological microscope. The results of our study showed that the immobilization capability and reactivity of APTES, APTES + BMS and APTES + OFPOS differ. The modification of APTES with unreactive silanes (BMS,OFPOS) is recommended to improve the antibody binding efficiency. However, using OFPOS resulted in more effective antibody and cell binding, and it appears to be the most useful compound in specific antibody-mediated cell recognition.